2015
DOI: 10.1007/s11606-015-3484-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Navigation on Breast Cancer Screening Among African American Medicare Beneficiaries: A Randomized Controlled Trial

Abstract: BACKGROUND:There is growing evidence that patient navigation improves breast cancer screening rates; however, there are limited efficacy studies of its effect among African American older adult women. OBJECTIVE: To evaluate the effect of patient navigation on screening mammography among African American female Medicare beneficiaries in Baltimore, MD. DESIGN: The Cancer Prevention and Treatment Demonstration (CPTD), a multi-site study, was a randomized controlled trial conducted from April 2006 through December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
97
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 50 publications
0
97
0
1
Order By: Relevance
“…2 Marshall et al report a randomized community-based intervention using patient navigators among African American women in Baltimore that increased breast cancer screening compared to receipt of printed materials. 3 These results add to the growing body of evidence supporting patient navigation as an effective tool for improving cancer screening rates among vulnerable populations. 4 The study is strengthened by randomization of the intervention, which enables the authors to avoid pre-and postintervention comparisons that can be biased by temporal trends.…”
mentioning
confidence: 74%
“…2 Marshall et al report a randomized community-based intervention using patient navigators among African American women in Baltimore that increased breast cancer screening compared to receipt of printed materials. 3 These results add to the growing body of evidence supporting patient navigation as an effective tool for improving cancer screening rates among vulnerable populations. 4 The study is strengthened by randomization of the intervention, which enables the authors to avoid pre-and postintervention comparisons that can be biased by temporal trends.…”
mentioning
confidence: 74%
“…Many practitioners have addressed medical issues within churches [14], community fairs, community organizations [15], beauty salons [16,17] and schools [18] embedded in AA communities. While these aforementioned efforts have been documented as effective, they have predominantly targeted women and children.…”
Section: Barbershop Model Effectivenessmentioning
confidence: 99%
“…One PNRP site was Chicago [6, 7], which exhibited increasing disparities due to differential access to technological advances in breast cancer care [810]. PNRP and other efficacy studies have subsequently demonstrated navigation is effective for improving breast cancer care uptake and time to diagnostic resolution [1122]. …”
Section: Introductionmentioning
confidence: 99%
“…First, with the exception of the Denver PNRP [17], extant individual- level RCTs to evaluate the efficacy of navigation have been relatively small (<250 participants total) [19, 18, 21, 20] or have relied on self-report outcomes [22]. There is a need for more large individual-level RCTs, especially those relying on medical records, to confirm the effects of navigation.…”
Section: Introductionmentioning
confidence: 99%